Language preference and reinforcing efficacy of praise in bilingual children with disabilities. Issue 1 (10th July 2019) - Clay, Casey J.; Bloom, Sarah E.; Slocum, Timothy A.; Samaha, Andrew L.; Callard, Chase H.
Abstract : We conducted a stimulus preference assessment to identify preference for praise delivered in English versus Spanish for bilingual students. Next, a concurrent‐operant reinforcer assessment was used to evaluate the reinforcer efficacy of praise in each language. Participants showed limited to no preference for one language over another. One participant showed a slight preference for Spanish praise and Spanish praise functioned as a slightly more potent reinforcer. If a participant did not prefer a specific language of praise (i.e., undifferentiated preference or equal percentage of approaches), both languages were considered to be similarly reinforcing.